2005
DOI: 10.5860/crl.66.3.248
|View full text |Cite
|
Sign up to set email alerts
|

Relative Influence of the LibQUAL+™ Dimensions on Satisfaction: A Subgroup Analysis

Abstract: This research study investigates the influence of the identified LibQUAL+™ dimensions on various aspects of the user's satisfaction with the Academic Library at Wayne State University. Multivariate regression analysis results show statistically significant impact of LibQUAL+™ dimensions on user satisfaction. Moderated regression analysis results show the moderating impact of various demographic variables on the relationships between LibQUAL+™ dimensions and user satisfaction. The results of this research can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Despite the problems with unidimensionality identified in this study, the subsequent psychometric analysis of the LibQUAL+ TM scale indicates high reliability (internal consistency) and good convergent, discriminant and nomological validity. The present findings are consistent with the results of previous studies that have supported the reliability of LibQUAL+ TM Heinrichs et al, 2005). However, very few studies have shown evidence of the construct validity of the scale.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Despite the problems with unidimensionality identified in this study, the subsequent psychometric analysis of the LibQUAL+ TM scale indicates high reliability (internal consistency) and good convergent, discriminant and nomological validity. The present findings are consistent with the results of previous studies that have supported the reliability of LibQUAL+ TM Heinrichs et al, 2005). However, very few studies have shown evidence of the construct validity of the scale.…”
Section: Discussionsupporting
confidence: 95%
“…A second category includes reports on practical applications and uses of LibQUAL+ TM (e.g. Heinrichs, Sharkey, & Lim, 2005;Kayongo & Jones, 2008). A third category consists of studies of the integrity, factor structure, reliability and validity of the instrument (e.g.…”
Section: Studies Of Libqual1 Tmmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent efforts to assess library use and user satisfaction have involved the use of the LibQUALϩ instrument. The LibQUALϩ instrument includes various measures related to the use of electronic access to materials, Web site usage, and electronic information access tools (Cook, Heath, Thompson, & Thompson, 2001;Heinrichs, Sharkey, & Lim, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The observed difference between genders at UW was significant in library instruction and computer access (Hiller, 2001). As Heinrichs et al (2005) state, "results at this point PMM 9,2 do not let library researchers draw a firm conclusion. As such, gender differences represent a potential area of future exploration".…”
Section: Surveys Of Gender Differencesmentioning
confidence: 96%